2019
DOI: 10.1007/s40618-019-01028-3
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genotyping of Turkish women with hirsutism

Abstract: Introduction Hirsutism is a medical sign rather than a disease affects 5-8% of women of reproductive age. Hirsutism is associated with hyperandrogenemia in most patients excluding those with idiopathic hirsutism (IH). The most common cause of hirsutism is polycystic ovary syndrome (PCOS) followed by IH and idiopathic hyperandrogenemia (IHA); however, the clinical presentation of non-classical congenital adrenal hyperplasia (NCAH) in females is often indistinguishable from other hyperandrogenic disorders with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 59 publications
(69 reference statements)
0
12
0
1
Order By: Relevance
“…These studies were carried out in Europe, the United States of America, and Russia. Three studies were carried out in Greece ( 15 , 30 , 31 ), three in the United States of America ( 18 , 32 , 33 ), two in Italy ( 34 , 35 ), two in Brazil ( 36 , 37 ), two in France ( 38 , 39 ), one in Turkey ( 21 ), one in Russia ( 40 ) and one in Israel ( 41 ). CYP21A2 mutation analysis and basal and/or stimulated 17-OHP measurements were available in all study subjects.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies were carried out in Europe, the United States of America, and Russia. Three studies were carried out in Greece ( 15 , 30 , 31 ), three in the United States of America ( 18 , 32 , 33 ), two in Italy ( 34 , 35 ), two in Brazil ( 36 , 37 ), two in France ( 38 , 39 ), one in Turkey ( 21 ), one in Russia ( 40 ) and one in Israel ( 41 ). CYP21A2 mutation analysis and basal and/or stimulated 17-OHP measurements were available in all study subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Determination of carrier status is also compulsory for genetic counselling of the parents affected by CAH/NCAH and in families that includes a parent with confirmed heterozygous mutation, since genetic counselling plays an important role in the control of genetic diseases. The heterozygous individuals may be diagnosed with NCAH due to false-positivity of the SDSST, especially in V281L heterozygous mutation ( 21 ). Therefore, there is a need for up-to-date studies on the specificity and sensitivity of the SDSST to distinguish CYP21A2 carriers and 21OHD-NCAH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In studies examining the genetic structure of Anatolia, it was found that hirsutism is a common problem, and in some accompanying clinical findings it was reported to have negative effects on life and marriage. (Salman KE, 2017;Polat S, 2019;Demir B, 2011) This study was conducted to investigate the self-esteem, sexual self-efficacy, anxiety and depression levels of women with hirsutism.…”
Section: Introductionmentioning
confidence: 99%